Penjatuhan Pidana Tambahan dengan Sistem Pemberatan Pidana Militer pada Kasus Tindak Pidana Disersi - Andayani, Lily; Ikrardini, Zulfika (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The imposition of an additional criminal penalty in the form of dishonorable discharge from military service on perpetrators of desertion is within the judge's authority, even though related desertion regulations may allow the perpetrator not to be discharged. The judge has the discretion to consider the nature and essence of the defendant's actions, which are deemed unfit to be retained in military service. This dismissal is seen not only as an administrative sanction but also as an effective preventive strategy against deviant behavior among soldiers, while providing legal certainty for recidivists of the criminal act of desertion. This research uses a normative juridical method with document study as the data collection technique, involving relevant legislation and court decisions. The analysis is carried out qualitatively and normatively and presented descriptively. The results indicate that dismissal can be an effective preventive measure, supporting the enforcement of military discipline, and providing a deterrent effect against similar future violations.